Pharmacological mechanism of natural antidepressants: the role of epigenetic modifications - Lu, Yitong; Shang, Ruirui; Zhong, Xia; Shi, Jingbo; Zhang, Guangheng; Zhao, Weijie; Teng, Jing (Frontiers in Pharmacology, 2025)
MDD is a complex mental illness shaped by the interplay between genetic vulnerability and environmental triggers. Its underlying pathophysiological processes are now understood to be influenced by epigenetic mechanisms. Growing evidence points to critical roles for DNA methylation, histone modification, and ncRNAs in driving transcriptional dysregulation within key brain regions implicated in MDD. These epigenetic alterations may underlie the persistent impairments in neuroplasticity following environmental stress exposure. NPs, renowned for their multi-target properties, have demonstrated promise in modulating epigenetic processes. However, a systematic synthesis of their regulatory roles, mechanisms, and therapeutic potential remains incomplete. This review aims to bridge this gap by integrating evidence from PubMed, Web of Science, and Embase databases to elucidate the role of epigenetic modifications in the pathogenesis and progression of MDD, dissect the mechanisms through which NPs exert antidepressant effects via epigenetic regulation, and highlight current research limitations while proposing strategies for translational applications in both preclinical and clinical settings.